Mapping North-South Relations: The Case of Australia’s Regional Refugee Arrangements - Dimas Fauzi; Yusnia Kurniasih (Global South Review, 2015)
In recent years, Australia has created some regional refugee arrangements with their neighbouring countries. Under the agreements with countries such as Nauru, Papua New Guinea, Malaysia and the most recent, Cambodia, Australia is committed to providing financial aid to run the supporting facilities and protect the asylum seekers who are relocated from their territory. These agreements then become questionable as the partner countries are developing countries which are relatively unstable in domestic politics and are not prosperous enough to bear the non-financial costs of refugee protection, such as integration and accountability issues. In this case, relations between Australia and their partner countries could be considered as an example of relations between the developed (north) and the developing countries (south). Thus, a question appears to be prominent: what do Australia refugee settlement agreements tell us about the relations between the (developed) north and the (developing) south? By employing structuralism model in international politics, we propose an argument that Australia’s refugee resettlement agreement can be understood as a form of responsibility sharing on refugee issue between the concerning countries in the region. The arrangements have not only produced positive results but also negative ones, such as conflicts. Additionally, this research will also take into account the existence of international law(s) governing refugee issues as the basis to analyse the refugee protection, mainly in Australia’s resettlement partner countries.